Pondering Pottery – Elemental Characterization of Early Eneolithic Pottery from Šanac–Izba near Lipolist - Marković, Nikola A. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Pottery from the site of Šanac–Izba near Lipolist was examined to reveal its chemical content. The site is located in western Serbia, Šanac–Izba near Lipolist. It was a small settlement only 40m in diameter and surrounded by a ditch. During the excavations in 2013 four pits and the remains of one burnt building were discovered. The site dates to the Early Eneolithic according to the regional chronology, late 5th millenium BC. Though three of the pits were of an unknown, yet later date. The pottery from the site is characterized by a diverse mix of cultural types that originate from the central Balkans and the southern Pannonian Basin. In particular, Bubanj and Tisapolgar culture influence is to be noted. Diagnostic fragments of pottery were sampled and analyzed for two key reasons. One, is there a significant difference in the chemical profile between the different pottery types? And two, can a chemical variability be observed between pottery that belong to different cultures? Forty one samples were selected based on their typology and in a way that represents all of the site features. Afterwards the samples were powdered and examined by pXRF and the results were statistically processed. According to the results, there is no significant difference in chemical profile between different pottery types nor is there a significant difference between different cultural traditions. Albeit, there was a single fragment of a storage vessel with calcium values that were several times higher than the average. Most likely this vessel (and its content) came to the site trough exchange, marital ties or as a gift.